Inferior alveolar nerve bypass during tilted implant insertion: A 3-year retrospective cohort study - Nadim Sleman (Elsevier, 2025)
Objective: Implant placement in atrophic mandibles can be challenging due to insufficient bone volume. To overcome this problem, bone grafts are often required to increase bone volume and provide a stable base for the implant. However, bone grafting procedures can be invasive, time-consuming, and costly. Tilted implants are a viable option to bypass the inferior alveolar nerve (IAN) and increase the contact surface and primary stability.The aim of this study was to evaluate the survival rate of tilted implants in posterior atrophic mandible and complications related to injury of the inferior alveolar nerve (IAN). Methods: Accepted patients in this study were only those who suffered from teeth loss in the posterior atrophic mandible. The analysis of this study focused on tilted implants to investigate the survival rate following insertion and during the loading stage. Clinical assessment was conducted to analyze any occurrences of IAN injury. Results: A total of 31 implants were placed in the posterior mandible of 26 patients with insufficient bone volume. Over a 36-month observation period, all implants exhibited a 100 % survival rate. Three patients experienced temporary neurosensory disturbances. Conclusions: The use of tilted implants is a viable option for patients with atrophic edentulous mandible that lack the required alveolar height for traditional dental implants. Despite limited study observation time, bypassing the IAN during implant placement presents a predictable option for atrophic posterior mandible treatment.